Les régimes de retraite et les législations s’y rapportant - Le Houillier, Marcel (Assurances)

(untitled) (HEC Montréal, 1983)
Mr. Marcel Le Houillier discusses retirement programs and the applicable legislation. The article is of particular interest as it is possible that there will be a reform of the large number of laws governing group retirement plans in Canada. The author describes current programs and legislation.